Risk assessment of floods on infrastructure system - Jiang, Wanzhen (2010)
Flood damage assessment and mitigation is essential for flood prone countries. Worldwide damages contribute to tangible and intangible damages that need to be assessed before and after a flood event. Derivation of damage-curves is important for damage assessment and parameters should be taken appropriately to suit each country. Flood damage assessment also helps in cost-benefit analysis for mitigation methods. Localized mitigation methods of structural and non structural form should be taken into consideration for a holistic approach to effective flood management. An analysis of Chiang Mai, Thailand, based on a case study of Bangkok, Thailand, is carried out to demonstrate the importance of both damage assessment and also mitigation measures in reducing flood losses.